A Case Study of Stevens–Johnson Syndrome-Toxic Epidermal Necrolysis (SJS-TEN) Overlap in Mycoplasma pneumoniae-Associated Tracheobronchitis. (30th May 2019) - Sah, Ranjit; Neupane, Samikshya; Khadka, Shusila; Poudyal, Sagar; Paneru, Hem Raj; Sah, Ranjana; Sah, Sanjit; Pant, Vivek
Abstract : Stevens–Johnson syndrome is a medical emergency which is characterized by skin and mucosal reaction to the use of certain drugs. Atypical Steven–Johnson syndrome can occur due to various microorganisms and Mycoplasma pneumoniae being one of them. We present a clinical course, diagnosis, and successful management of Steven–Johnson syndrome-toxic epidermal necrolysis (SJS-TEN) overlap due to Mycoplasma pneumoniae in a 17-year-old Nepalese female. In the resource-limiting country and hospitals where serology and PCR for M. pneumoniae is not easily accessible, a simple bedside cold agglutination test can be done to increase the suspicion of infectious cause (most common M. pneumoniae ) of SJS-TEN overlap. M. pneumoniae infection should be considered in all cases of mucositis, especially in patients having preceding respiratory tract infections (tracheobronchitis).